2015
DOI: 10.3389/fmicb.2015.00910
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbapenem-resistant Acinetobacter baumannii isolates in a Chinese teaching hospital

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB) presents a serious therapeutic and infection control challenge. In this study, we investigated the epidemiological and molecular differences of CRAB and the threatening factors for contributing to increased CRAB infections at a hospital in western China. A total of 110 clinical isolates of A. baumannii, collected in a recent 2-year period, were tested for carbapenem antibiotic susceptibility, followed by a molecular analysis of carbapenemase genes. Genetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 60 publications
7
54
2
3
Order By: Relevance
“…Epidemiological analysis of the 34 patients with carbapenem-resistant Acinetobacter spp indicated that 7 were ≥71 years old, 8 were between 61 and 70 years old, 5 were between 51 and 60 years old, 11 were between 21 and 50 years old, and 3 were ≤20 years old, with an average age of 47.6 years (SD = 21.31), ranging from 17-86 years, which was comparable to what was observed in other studies (48, 54, and 53.2 years; Wisplinghoff et al, 2000;Sunenshine et al, 2007;Godoy, 2012). In the patient sample, 20 were male (58.8%) and 14 were female (41.2%), supporting reports by Chang et al (2015) that males have a higher risk of infection than females. Analyzing the principal complaint related to patient admission, nine had hematological or solid neoplasms, eight had suffered trauma, five had neurological diseases, four had skin lesions (of which two were large burns), six had assorted clinical complaints (cardiac, respiratory, renal, digestive, metabolic), and two had been admitted due to post-surgery complications.…”
Section: Epidemiological Profile Of the Patients And Their Acinetobacsupporting
confidence: 83%
See 3 more Smart Citations
“…Epidemiological analysis of the 34 patients with carbapenem-resistant Acinetobacter spp indicated that 7 were ≥71 years old, 8 were between 61 and 70 years old, 5 were between 51 and 60 years old, 11 were between 21 and 50 years old, and 3 were ≤20 years old, with an average age of 47.6 years (SD = 21.31), ranging from 17-86 years, which was comparable to what was observed in other studies (48, 54, and 53.2 years; Wisplinghoff et al, 2000;Sunenshine et al, 2007;Godoy, 2012). In the patient sample, 20 were male (58.8%) and 14 were female (41.2%), supporting reports by Chang et al (2015) that males have a higher risk of infection than females. Analyzing the principal complaint related to patient admission, nine had hematological or solid neoplasms, eight had suffered trauma, five had neurological diseases, four had skin lesions (of which two were large burns), six had assorted clinical complaints (cardiac, respiratory, renal, digestive, metabolic), and two had been admitted due to post-surgery complications.…”
Section: Epidemiological Profile Of the Patients And Their Acinetobacsupporting
confidence: 83%
“…The genus Acinetobacter is widely distributed in nature (Baumann, 1968;Ferreira et al, 2011) and includes 37 different species (Peleg et al, 2008). Among these, Acinetobacter baumannii is the most clinically relevant species (Martins and Barth, 2013) and has emerged as a major problem in health institutions due to its ubiquity, difficult eradication (resistance to desiccation, chemical sanitizers, and ultraviolet) (Cherkaoui et al, 2015), and high tendency to acquire resistance to antibiotics (Peleg et al, 2008;Chang et al, 2015). This species is responsible for nosocomial infections, especially by cross transmission, and has a propensity to cause outbreaks (Khorsi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…baumannii is an opportunistic pathogen primarily associated with nosocomial infections worldwide (17). In addition to causing broad range of infections (eg, pneumonia, urinary tract, bloodstream, and skin infections), this organism is responsible for 10% of all nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%